2010
DOI: 10.1017/s0950268810001706
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of dengue virus type 4 (genotype I) in India

Abstract: Dengue is an emerging arboviral disease and currently poses the greatest arboviral threat to human health. In recent decades, there has been a substantial increase in dengue outbreaks in many parts of the world including India. We performed an in-depth investigation of a major dengue outbreak in Andhra Pradesh, southern India in 2007 by serology, virus isolation, RT-PCR and genotyping. The results revealed an unusual emergence of dengue virus type 4 (DENV-4) along with the prevailing DENV-3. Phylogenetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
58
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 14 publications
13
58
0
1
Order By: Relevance
“…4). Genotype III of DENV-3 is of Indian origin (Messer et al, 2003), and this strain has been suspected to cause more fatal infections (Dash et al, 2005). Two lineages of this genotype were recorded in the present study in Kerala.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…4). Genotype III of DENV-3 is of Indian origin (Messer et al, 2003), and this strain has been suspected to cause more fatal infections (Dash et al, 2005). Two lineages of this genotype were recorded in the present study in Kerala.…”
Section: Discussionmentioning
confidence: 47%
“…Previously, it was reported that DENV-2 was the major serotype circulating in India (Dar et al, 1999;Kumar et al, 2001). Recently, DENV-3 has emerged as the major serotype in different parts of the country (Dash et al, 2005). Due to a lack of studies in Kerala before the 2008 outbreak on the genetic characterization of the virus, we are unable to arrive at a conclusion on the evolutionary trends of different serotypes in Kerala.…”
Section: Discussionmentioning
confidence: 96%
“…8 Mean age group of present study is 29.3 years youngest was 18 years and oldest was 50 years and age group that is mostly affected in other studies like Gupta et al New Delhi was 5-20 years, Dash PK et al Gwalior was <15 years, and Neeraja M in Hyderabad was 20 -39 years. [9][10][11] In this study most of the patients are males (64) in comparison to females (36) and ratio is 1.7:1. In other studies like Dash PK et al, Gwalior male female ratio was 1.28:1, Neeraja M Hyderabad was 2:1, Gupta et al New Delhi, was 1.8 :1.…”
Section: Resultsmentioning
confidence: 94%
“…Difference in this may be due small number of patients taken in this study group or it may be due to because of male dominated region where male seeks more medical help in comparison to females. [9][10][11] This needs study with more numbers of patients.…”
Section: Resultsmentioning
confidence: 99%
“…3 The largest Dengue outbreak in India which occurred in 1996, was due to DENV-2. 4 This was later replaced by 5 The subsequent outbreaks witnessed a mixed type of infection with DENV-1, 2 and 3. 6,7 We present the seroprevalence of Dengue virus referred to a tertiary care hospital from in and around Government and private hospitals and clinics of Hyderabad and Districts surrounding Hyderabad for a period of 18 months.…”
Section: Introductionmentioning
confidence: 99%